Percepção materna de vínculo, crenças e práticas em situação de vulnerabilidade social - Gomes, Jeanne Arina Meytre (2018)
Culture-related beliefs influence the way mothers interpret childhood behavior, and the bond they develop with the child are determinant in the formation of the human being. In this sense, studies about bonding, beliefs and practices in different contexts can contribute to the promotion of child development. Objective: The objective of this study was to evaluate the maternal perceptions of bonding, beliefs and practices adopted in the care of children in situations of social vulnerability; assisted by NGOs that attend early childhood in Fortaleza - CE. Method: A cross-sectional, quantitative, descriptive study with 221 mothers and their children between 0 and 35 months. To obtain the data, we used the Parental Beliefs and Care Practices Scale(E-CPPC) and the Psychometric Evaluation of Maternal Attachment Inventory; moderating variables were obtained through the Sociodemographic Questionnaire (SRQ-20) and the Brazilian Food Insecurity Scale (EBIA). Results: The results indicated that mothers in the context of social vulnerability, mostly beneficiaries of governmental income transfer programs and food insecurity at home, performed more primary care practices than stimulation. The data on the practices and beliefs about stimulation in the criterion above the average, indicate that 55.66% of the mothers stimulate their children, however only 29.86% of the mothers declare to find the stimulation important. When data are divided by age group, there is a considerable reduction in "above-average" frequency for stimulation beliefs: from 0 to 18 months, only 16.5% of mothers value stimulation, with an increase to 38.2 % in the age group of 19 to 35 months. In the aspect of “maternal attachment” there is a certain similarity in the factors of “interaction and affection” and “maternal perception”, and association (Prevalence Ratio) with care and stimulation practices, as well as positive interference with the increase in per capita income and maternal schooling. Conclusions: The study indicated a positive influence bythe increase in per capita income and maternal schooling as factors related to maternal attachment; mothers in a context of social vulnerability have less stimulation beliefs compared to care beliefs, especially in children up to 18 months.